Improving Children’s Social Interaction Through Group Work Method in Group B of Gunung Bale State Kindergarten - Anggraeni, Anggraeni; Agusniatih, Andi; Amrullah, Amrullah; Zuama, Shofiyanti Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aimed to improve children’s social interactions through the application of the group work method in Group B of Gunung Bale State Kindergarten, Donggala. Conducted in July 2025, the research involved 15 children—7 boys and 8 girls—and employed a classroom action research design consisting of four stages: planning, action, observation, and reflection. The research process was divided into three phases: pre-action, Cycle I, and Cycle II, to observe the extent of change in children’s social interaction skills. The observed aspects included helping each other, cooperation, understanding conversations, and communication. The results revealed a significant improvement from the pre-action stage to Cycle II. The percentage of children categorized as “Very Well Developed” increased from 23.33% in Cycle I to 45.00% in Cycle II, while those in the “Not Yet Developed” category decreased from 35.00% to 3.33%. These findings demonstrate that the group work method effectively enhances children’s social interaction skills and serves as an alternative learning strategy in early childhood education.